2022
DOI: 10.1038/s41467-022-29144-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes in the Challenger Deep slope and bottom-axis sediments

Abstract: Hadal trenches are the deepest and most remote regions of the ocean. The 11-kilometer deep Challenger Deep is the least explored due to the technical challenges of sampling hadal depths. It receives organic matter and heavy metals from the overlying water column that accumulate differently across its V-shaped topography. Here, we collected sediments across the slope and bottom-axis of the Challenger Deep that enable insights into its in situ microbial communities. Analyses of 586 metagenome-assembled genomes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 106 publications
5
70
0
Order By: Relevance
“…The in silico host prediction indicated that CD viruses may infect 42 of our CD MAGs, assigned at 27 taxa at the species level (spanning seven phyla). These taxa include heterotrophs (e.g., Proteobacteria) and chemoautotrophs (e.g., Thaumarchaeota, Planctomycetota) involved in nitrogen and carbon cycling whose taxonomic signatures were abundant in CD sediments 39 , but with different relative abundances (7% to 43%) across the discrete sampling sites (bottom-axis vs. slope) (Supplementary Data 7 ). Indeed, Proteobacteria, Thaumarchaeota, and Planctomycetota were the most frequently predicted hosts in CD sediments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The in silico host prediction indicated that CD viruses may infect 42 of our CD MAGs, assigned at 27 taxa at the species level (spanning seven phyla). These taxa include heterotrophs (e.g., Proteobacteria) and chemoautotrophs (e.g., Thaumarchaeota, Planctomycetota) involved in nitrogen and carbon cycling whose taxonomic signatures were abundant in CD sediments 39 , but with different relative abundances (7% to 43%) across the discrete sampling sites (bottom-axis vs. slope) (Supplementary Data 7 ). Indeed, Proteobacteria, Thaumarchaeota, and Planctomycetota were the most frequently predicted hosts in CD sediments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). This can be attributed to differences in the geographical isolation and nutrient availability between slope and bottom-axis sites that have been suggested to affect the distribution of prokaryotic communities across the V-shaped CD trench 38,39 . Differences in viral communities at discrete depths observed in this study and between this study and upper CD slope 48 15 and three hadal trenches 30 ), wetland 46 , thawed permafrost 47 , and pelagic seawater (Global Ocean Viromes 2.0) 7 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except participating in the energy metabolism, viruses also encode unique antibiotic gene (PrnA) and virulence factors for bacterial immune reaction (Figures 6B and 6C). In addition, viruses in deep and hadal zones might be involved in the arsenic-related biological process (Figure 6), which was recently detected in the metagenomic assembled microbial genomes and proposed to relate to the biotransformation of arsenate for energy gain in the hadal sediments (Zhou et al, 2022). Comprehensive, viruses might influence the hadal microbial community structure and metabolism through the expression of AMG relating to antibiotic biosynthesis and nutrient metabolism to elevate the microbial adaption to the extreme environment in the hadal oceans (Figure 6).…”
Section: High Levels Of Lysogeny and Potential Horizontal Gene Transf...mentioning
confidence: 95%